Early diagnostics of infectiouscomplications in injured persons with heavy traumas - S. A. Svistunov; A. A. Kuzin; T. N. Suborova; I. M. Samokhvalov; A. A. Rud`; D. A. Zharkov (Журнал инфектологии)
In this study specific features of the etiological structure of infectiouscomplications occurring early in treatment of heavily injured patients is established and the need is demonstrated for bacteriological examination of clinicalmaterials according to a developed algorithm on the second or third day after admission to hospital, which contributes totimely isolation of etiological agents of infectiouscomplications, rational etiotropic antibacterial treatment and reduced mortality.